Avoiding wasted research resources in conservation science. Issue 2 (29th January 2021) - Buxton, Rachel T.; Nyboer, Elizabeth A.; Pigeon, Karine E.; Raby, Graham D.; Rytwinski, Trina; Gallagher, Austin J.; Schuster, Richard; Lin, Hsien‐Yung; Fahrig, Lenore; Bennett, Joseph R.; Cooke, Steven J.; Roche, Dominique G.
Abstract: Scientific evidence is fundamental for guiding effective conservation action to curb biodiversity loss. Yet, research resources in conservation are often wasted due to biased allocation of research effort, irrelevant or low‐priority questions, flawed studies, inaccessible research outputs, and biased or poor‐quality reporting. We outline a striking example of wasted research resources, highlight a powerful case of data rescue/reuse, and discuss an exemplary model of evidence‐informed conservation. We suggest that funding agencies, research institutions, NGOs, publishers, and researchers are part of the problem and solutions, and outline recommendations to curb the waste of research resources, including knowledge co‐creation and open science practices.